Comparative Evaluation of the Cyclic Fatigue Resistance of Thermally Treated Nickel-Titanium (Ni-Ti) instruments at Varying Temperatures - Sandeep Metdud; Aasima Ishaq; Afzal Ali (Atatürk University, 2024)
Objective: This study aimed to evaluate the stationary cyclic fatigue resistance (CFR) of three endodontic instrument systems at varying temperatures (20 ± 1°C and 37 ± 1°C).. Methods: Ninety endodontic instruments from three instrument systems (HyFlex CM, 2Shape and Hero Gold) of constant tip size and taper (25.04) were selected for this study. These systems were broadly, divided into three groups (n=30): Group 1 (Hyflex CM), Group 2 (2Shape) and Group 3 (Hero Gold). Each group was further subdivided into two subgroups based on the temperature variable used. The endodontic instruments were subjected to stationary cyclic fatigue testing at 20 ± 1°C and 37 ± 1°C using a stainless-steel block with an artificial canal. The number of cycles to failure (NCF) were recorded Results: Data was analysed using two-way ANOVA and Tukey post-hoc tests at a 95% confidence level. The instrument type and temperature variable significantly affect the NCF values. The observed NCF of the tested instruments was higher at 20±10 °C compared to its values at 37±10 °C and was statistically significant. The HyFlex CM group exhibited the highest CFR at 20±10 °C, while at 37±10 °C the Hero Gold instruments exhibited a higher CFR. Conclusion: It can be inferred that Hero Gold instruments exhibited superior clinical performance when compared with Hyflex CM and 2Shape rotary instruments at body temperature (37±10 °C). The observed reduction in the NCF when increasing the temperature ranges between 30.29% - 71.27%.. Keywords: Cyclic Fatigue Resistance, Hero Gold, Hyflex CM, Nickel-Titanium, Stationary Fatigue, and 2Shape ÖZ Amaç: Bu çalışma, üç endodontik alet sisteminin değişen sıcaklıklarda (20 ± 1°C ve 37 ± 1°C) sabit yorulma direncini (CFR) değerlendirmeyi amaçladı Yöntemler: Bu çalışma için sabit uç boyutu ve konikliğe (25,04) sahip üç alet sisteminden (HyFlex CM, 2Shape ve Hero Gold) doksan endodontik alet seçildi. Bu sistemler genel olarak üç gruba ayrıldı: Grup 1 (Hyflex CM), Grup 2 (2Shape) ve Grup 3 (Hero Gold). Her grup ayrıca kullanılan sıcaklık değişkenine bağlı olarak iki alt gruba bölündü. Endodontik aletler, yapay kanallı paslanmaz çelik bir blok kullanılarak 20 ± 1°C ve 37 ± 1°C'de sabit döngüsel yorulma testine tabi tutuldu. Arızaya kadar olan döngü sayısı (NCF) kaydedildi Bulgular: Veriler, iki yönlü ANOVA ve Tukey post-hoc testleri kullanılarak %95 güven seviyesinde analiz edildi. Alet tipi ve sıcaklık değişkeni NCF değerlerini önemli ölçüde etkiler. Test edilen cihazların gözlenen NCF'si 20±10 C'de 37±10 C'deki değerlerine göre daha yüksekti ve istatistiksel olarak anlamlıydı. HyFlex CM grubu en yüksek CFR'yi 20±10 C'de sergilerken, 37±10 C'de Hero Gold aletleri daha yüksek bir CFR sergiledi Sonuç: Hero Gold aletlerinin vücut sıcaklığında (37±10 C) Hyflex CM ve 2Shape döner aletlerle karşılaştırıldığında üstün klinik performans sergilediği söylenebilir. Sıcaklık artırıldığında NCF'de gözlenen azalma %30,29 - %71,27 arasında değişmektedir. Anahtar Kelimeler: Cyclic Fatigue Resistance, Hero Gold, Hyflex CM, Nickel-Titanium, Stationary Fatigue, and 2Shape